Mellan sociologi och ekologi? Om det sociologiska studiet av miljöfrågan (Sociologisk Forskning, 1995)
Sociology, as it came to be constructed from the late 19th century onwards, deliberately concentrated on human societies, giving little attention to the natural world which constitutes the very condition of its existence and development. Today, some sociologists claim that the environmental problems of today constitute a challenge to this classical sociological understanding. By critically discussing environmental sociologists’ claim for the necessity to include biophysical facts in sociological analysis, this article seeks to elaborate a sociological perspective on environmental problems. From the point of view of epistemology and the sociology of knowledge, the article contrasts naive realism with social constructivism. It is here stated that even though social constructivism seems to be more in line with sociological thought a realistic standpoint regarding the environmental threat seem to be a necessity. By way of conclusion it is stated that a proper sociological understanding has to take into account nature’s constructedness as well as realistic side. Thus nature cannot be understood outside of society or society outside of nature.